Hydrogen production through electrolysis using the very high temperature reactor - Xie, Lei. (2011)
Hydrogen is already an important and long-established raw material for the chemical industry today. It has an important part to play in the manufacture of synthetic fuels, as a substitute for ever more costly petroleum products. With hydrogen as a future means of energy storage, nuclear energy and new energy sources could be better utilized. The study of nuclear plant design such as the technology being used, nuclear fuel, nuclear cooling system etc and the study of hydrogen production process was discussed based on past research. Hydrogen production using high-temperature steam electrolysis (HTSE) supported by a supercritical CO2 (SCO2) recompression Brayton cycle that is directly coupled to an advanced gas-cooled reactor (AGR) is proposed in this paper.